A statistical analysis study on JSG & Sons Concrete Products, Inc. - Florendo, Michael L.; Galang, Myrtle Holiday D.; Turay, Dahlia U. (Diliman, Quezon City College of Engineering, 2002)
JSG & Sons Concrete Products, Inc. started out as a small business of gravel and sand in 1948. The business grew through the years and expanded into the manufacture of concrete hollow blocks and pipes. Today, the company is one of the leading manufacturers of concrete products in the country and is a reliable supplier of concrete pipes to various private and government institutions. This study aims to improve the existing production system of the company and solve their problem concerning the high number of rejected pipes. The study focused on the reinforced concrete pipe of Class II Wall B with internal diameter of 24 inches which comprises more than 25 percent of the company's production. It was found out using the Pareto Diagram that the high rejection of pipes is mainly due to the failure of the pipes to pass the strength requirement. Uisng the Ishikawa Diagram, it was found out that the number of curing days, ratio of cement in the concrete mixture and the spacing and number of hoops in the reinforcement cage are the main factors that affect the strength of the concrete pipes. Due to inefficiency of data, only the effect of the cement ratio and the number of curing days to the strength of the pipes were studied using different statistical tests. The Analysis of Variance Two-Factor Factorial Design was used to determine the effects of the number of curing days and cement ratio to the D-load strength and Ultimate load of the pipe. The Duncan's multiple range test, test on two means, correlation and residual analysis were the other tests used in the study. Two cement proportions were used in the analysis. The result of the tests shows that ratio has a significant effect on the strength of the pipe. The higher cement ratio is recommended because it yields pipes with higher strength. For the analysis of the curing days, five different days were considered. The tests show that the number of curing days also has a significant effect on the strength, as the number of curing days increase, the strength of pipe also increases. The interaction of the curing days and the cement ratio however, did not show any significant effect. The group recommends that the proportion of cement in the mixture, the number of curing days and the spacing and number of hoops in the reinforcement cage should be monitored strictly to lessen the number of rejections and improve the quality of the pipes. Further studies about the Ultimate load and D-Load is suggested to establish their relationship. Other unverified factors such as the quality of the raw materials and the effect of the workers should also be monitored and studied if possible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics